Time to shine applications of solar energy technology - Grupp, Michael (Scrivener Pub. ; Co-published by Wiley, 2012)
"Solar energy has been the "new" energy for a long time. As this technology becomes a larger and larger piece of the energy spectrum, it is increasingly important for engineers, scientists, managers, and other decision-makers to understand solar energy technology and its applications. This book, written in easy-to-understand language, with plentiful color photos and illustrations, is the perfect primer on solar energy for anyone working in the energy industry or just wants to learn more about solar energy technology. With a focus on its current uses in other countries, including developing countries, this book shows examples of actual and potential uses of solar energy right here in the USA. It presents an original view of solar energy technology, as well as tools for the understanding of consequences of energy-related decisions. Parts of this book draw to a large extent on the work of the Synopsis Institute in Lodève (France), a leading research and development firm in the area of solar energy technology and its practical uses in our everyday lives"--